2018
DOI: 10.3389/fpls.2018.01792
|View full text |Cite
|
Sign up to set email alerts
|

BrLAS, a GRAS Transcription Factor From Brassica rapa, Is Involved in Drought Stress Tolerance in Transgenic Arabidopsis

Abstract: GRAS proteins belong to a plant-specific transcription factor family and play roles in diverse physiological processes and environmental signals. In this study, we identified and characterized a GRAS transcription factor gene in Brassica rapa, BrLAS, an ortholog of Arabidopsis AtLAS. BrLAS was primarily expressed in the roots and axillary meristems, and localized exclusively in the nucleus of B. rapa protoplast cells. qRT-PCR analysis indicated that BrLAS was upregulated by exogenous abscisic acid (ABA) and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Moreover, GRAS (located in Chr5:M-QTL4 and down-regulated in the roots) proteins belong to a plant-specific transcription factor family involved in many plant processes including plant growth and development as well as abiotic stress responses (Table S6 , Fig. 6 ) [ 49 , 50 ]. It has also been reported that MOC1 encodes a nuclear transcription factor from GRAS family.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GRAS (located in Chr5:M-QTL4 and down-regulated in the roots) proteins belong to a plant-specific transcription factor family involved in many plant processes including plant growth and development as well as abiotic stress responses (Table S6 , Fig. 6 ) [ 49 , 50 ]. It has also been reported that MOC1 encodes a nuclear transcription factor from GRAS family.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the fickle N-terminus of GRAS proteins could be folded and modified into specific molecular binding structures. Based on these, the GRAS proteins broadly participated in many critical processes such as signal transductions, root radial elongations, axillary shoot meristem formations and stress responses in plants [ 10 – 13 ]. Previously, the GRAS gene family in Arabidopsis thaliana was separated into eight subfamilies, including DELLA, SCL3, LAS, SCR, HAM, SHR, LISCL and PAT1 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…BrLAS is primarily expressed in roots and axillary meristems. Overexpression of the Brassica rapa gene BrLAS in Arabidopsis plants resulted in delayed bolting, flowering time, senescence, decreased fertility and enhanced drought resistance ( Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%